Hare in Sauce According to Anthimus’ Recipe: Meat - Rzeźnicka, Zofia (Studia Ceranea, 2022)
The present article examines the beginning of the recipe for hare meat (leporis vero si novellae […]) preserved in Chapter 13 of the dietetic treatise De observatione ciborum written in the first half of the 6th cent. by the Byzantine physician Anthimus.In the initial part of the study, the author briefly discusses key events in the doctor’s life, explaining the circumstances which brought him to the royal court of the Frankish ruler, Theuderic. Next, the author analyses Anthimus’ competence in the field of dietetics and proves that he composed his treatise in line with ancient and Byzantine materia medica.The key part of the article scrutinises the most popular methods of preparing hare meat according to ancient gastronomical literature (Ἡδυπάθεια by Archestratus of Gela, De re coquinaria) and compares them with Anthimus’ recommendations. This allows the author to reconstruct the culinary techniques that Anthimus most probably proposed be applied in the preparation of hare meat.The author concludes that Anthimus’ treatise is a clear example of the practical application of both dietetics and materia medica in culinary practices performed in the physician’s lifetime.